Nanospacers: Highly Intensified Surface Enhanced Raman Scattering by Using Monolayer Graphene as the Nanospacer of Metal Film–Metal Nanoparticle Coupling System (Adv. Funct. Mater. 21/2014). (June 2014) - Li, Xuanhua; Choy, Wallace C. H.; Ren, Xingang; Zhang, Di; Lu, Haifei
<x xml:space="preserve">Abstract</x> Ultrathin monolayer graphene as a welldefined sub‐nanospacer between Ag NPs and Ag film is demonstrated by C. H. Choy and co‐workers. Their results show that the system offers a tremendous near‐field enhancement with one of the highest enhancement ratios reported to date in the graphene–metal plasmonic combination system. There is an additional chemical enhancement from the interaction between graphene sub‐nanospacer and detection molecules. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>